Application of free side edges to thickness shear bulk acoustic resonator on lithium niobate for suppression of transverse resonances. (15th April 2021) - Wu, Ting; Wong, Yu-Po; Wu, Zhao-Hui; Bao, Jing-Fu; Hashimoto, Ken-Ya
Abstract: This paper discusses the applicability of free side edges to a thickness shear bulk acoustic resonators (TSBARs) on a rotated Y -cut lithium niobate plate for suppression of lateral energy leakage and the transverse mode resonances. It is shown both theoretically and experimentally that free edges are effective to suppress lateral leakage and transverse mode resonances in free-standing TSBARs. Although this technique is applicable only to the X side boundaries, it is shown that the Y′ side perpendicular to the X side can be designed for the piston mode operation independently by the simple two-dimensional analysis ignoring wave propagation toward the X direction. Then the discussion is extended to the solidly-mounted TSBAR. It is shown that this technique works well also for this case, and removal of the first few Bragg layers is enough for the transverse mode suppression.